Effect of pedal cadence on mechanical power output and physiological variables - Jefferson da Silva Novaes; Jorge Roberto Perrout de Lima; Luiz Alberto Batista; André Calil e Silva; José Marques Novo Júnior; Marcelo Ricardo Cabral Dias (Universidade Federal de Santa Catarina, 2007)
The objective of this study was to compare the responses of the variables maximal power output (POmax), heart rate (HR), rating of perceived exertion (RPE), systolic blood pressure (SBP), diastolic blood pressure (DBP) and double product (DP) in the maximum reached load and during 60 and 90 rev.min-1 tests. The study sample consisted of 14 men (26.5 ± 3.5 years, 78.5 ± 7.8 kg and 178.1 ± 7.0 cm) engaged in indoor cycling classes, who undertook two tests of maximum effort using Balke's incremental protocol. The fi rst test (test60) consisted of a pedal cadence of 60 rev.min-1 throughout the test, until voluntary exhaustion or the appearance of signs or symptom limits. The second test (test90) was at a pedal cadence of 90 rev.min-1. There were no signifi cant difference between the cadences tested in terms of HRmax (test60: 189.7±12.0 beats.min-1; test90: 190.9±10.7 beats.min-1), RPEmax (test60: 20.0±0.3; test90: 20.0±1.0) or DBPmean (test60: 76.7±4.9 mmHg; test90: 79.1 ± 5.3 mmHg). On the other hand, the values of POmax (test60: 344.6±70.1 W; test90: 285.7±61.8 W), SBPmax (test60: 186.1±14.7 mmHg; test90: 202.1±21.5 mmHg) and DPmax (test60: 35402.9±4431.7; test90: 38655.0±5270.5) were different. In relation to the behavior of the variables during the tests, there were signifi cant difference in HR between the tests up to a level of 225 W. It was observed that neither RPE or DBP indicated signifi cant difference in absolute power. There were only differences in SBP and DP between the cadences at 300 W absolute power. With this, it is clear that to carry out maximum tests, even in protocols that do not prescribe the pedal cadence, it appears thet a 60 rev.min-1 pedalling speed is indicated. ABSTRACT O objetivo deste estudo foi comparar as respostas das variáveis potência máxima (Pmax), freqüência cardíaca (FC), percepção de esforço (PE), pressão arterial sistólica (PAS), pressão arterial diastólica (PAD) e duplo produto (DP) na carga máxima atingida e durante os testes de 60 e 90 rpm. A amostra deste estudo constou de 14 homens (26,5 ± 3,5 anos, 78,5 ± 7,8 kg e 178,1 ± 7,0 cm) praticantes de aulas de ciclismo "indoor", que realizaram dois testes de esforço máximo, segundo o protocolo incremental de Balke. O primeiro teste (test60) consistiu de uma cadência de pedalada de 60 rpm até a exaustão voluntária ou o aparecimento de sinais ou sintomas limitantes. Já o segundo teste (test90) utilizou a cadência de pedalada de 90 rpm. Não houve diferença signifi cativa da FCmax (test60: 189,7±12,0 bpm; test90: 190,9±10,7 bpm), PEmax (test60: 20,0±0,3; test90: 20,0±1,0) e PADmédia (test60: 76,7±4,9 mmHg; test90: 79,1 ± 5,3 mmHg) entre as cadências testadas. Por outro lado, os valores de Pmax (test60: 344,6±70,1 W; test90: 285,7±61,8 W), PASmax (test60: 186,1±14,7 mmHg; test90: 202,1±21,5 mmHg) e DPmax (test60: 35402,9±4431,7; test90: 38655,0±5270,5) foram diferentes. Em relação ao comportamento das variáveis durante os testes, houve diferença signifi cativa da FC entre os testes até 225 W. Observou-se que tanto na PE, quanto na PAD, não houve diferença significativa em nenhuma potência absoluta. Para PAS e para o DP, houve diferença signifi cativa entre as cadências somente na potência absoluta de 300 W. Com isso, fi ca claro que realizar testes máximos, mesmo em protocolos que não prescrevam a cadência de pedalada, parece ser indicado pedalar a 60 rpm.